The Safety of Heparin-Free Strategy in Patients Supported by Venoarterial Extracorporeal Membrane Oxygenation - Kim, Dong Jung; Lee, Jae Hang; Kim, Jun Sung; Lim, Cheong; Park, Kay-Hyun; Chang, Hyoung Woo (Cardiology and Cardiovascular Medicine, 2023)
Background: The necessity of heparinization during venoarterial extracorporeal membrane oxygenation (VA-ECMO) is well documented. However, heparinization can increase the risk of bleeding in certain situations. The aim of this study was to investigate the safety of a heparinfree strategy in patients on VA-ECMO. Methods: Data for 90 adult patients on VA-ECMO, wherein cannulation and maintenance were performed by cardiothoracic surgeons and support was provided for >24 h (2018–2021), were retrospectively reviewed. Patients were divided into two groups: heparin-free group, without heparinization for ≥ 24 h during VA-ECMO support (n = 66), and control group (n = 24). Clinical outcomes including hemorrhagic and thromboembolic complications were compared between the two groups. Results: The reasons for VA-ECMO support included post-cardiotomy cardiogenic shock in 37 patients (41.1%), and extracorporeal cardiopulmonary resuscitation in 44 patients (48.9%). The total duration of VA-ECMO was not significantly different between the two groups (132.3±106.1 vs. 141.6±117.9 h, P=0.734). In the heparin-free group, the duration of VA-ECMO without heparinization was 79.8±60.7 h, and 26 patients (39.4%) were completely heparin-free during the support period. No significant difference was found in the frequency of oxygenator changes due to thrombosis between the two groups (8.3 vs. 10.6%, P>0.999). Pump malfunction was not observed in any group. The overall incidence of thromboembolic complications was not significantly different between the two groups. Conclusion: No additional risk of thromboembolic complications was observed with the use of a heparin-free strategy during VA-ECMO support. Appropriate discontinuation of heparinization could be a safe strategy for VA-ECMO patients with active bleeding or a high hemorrhagic risk.